Immediate impact of COVID-19 pandemic on farming systems in Central America and Mexico - López Ridaura, Santiago; Sanders, Arie; Barba-Escoto, Luis; Wiegel, Jennifer Rebecca; Mayorga-Cortes, Maria; González Esquivel, Carlos; López Ramirez, Martin A.; Escoto-Masis, Rene M.; Morales Galindo, Edmundo; García-Barcena, Tomas S. (Elsevier, 2021)
In this article we present a first attempt to understand the immediate impact of COVID-19 and the sanitary measures taken by governments on farming systems in Central America and Mexico (CAM). Through a review of information generated in these initial months of the COVID-19 pandemic (webinars, blogs, electronic publications, media) and 44 interviews with key informants across the region, we have identified the main impacts felt by different types of farming systems in the region. The results presented focus only in the immediate effect of COVID-19 pandemic and the mechanisms implemented by farmers in the first months. Whether these impacts and response mechanisms will result in a transformation of the farming systems towards greater resilience and sustainability is still an open question.